Analisis Faktor Penghambat Mahasiswa untuk Memulai Usaha Saat Masih Aktif di Perguruan Tinggi: Tinjauan dari Sudut Pandang Pengalaman dan Keterbatasan - Budiman, Arief (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to conduct an in-depth analysis of the factors that hinder students from starting a business while still active in higher education, taking into account the perspective of experience and the limitations they face. Qualitative research methods were used to collect data through in-depth interviews with a number of students who had faced obstacles in starting their business during college. The research results show that there are several factors that are the main obstacles, including limited academic time, limited capital and financial resources, risk uncertainty, lack of business experience, and lack of support and understanding from the surrounding environment, including family. The implication of these findings is the importance of developing more holistic entrepreneurship education programs and more intensive support from related parties to help students overcome these obstacles and start their businesses with more confidence and success.